Model Numerik Pengaruh Koefisien Kekasaran Manning Terhadap Kenaikan Muka Air di Teluk Palu - Prawirabhakti, Alamsyah; Andiese, Vera Wim (Jurusan Teknik Sipil Universitas Tadulako, 2015)
Manning roughness coefficient (n) is one of the parameters affecting the drainage conditions, such as speed and water level. These coefficients, in its natural state vary based on the size, shape and type of material. This study aims to look at the influence of changes in flow conditions due to the use of the Manning coefficient varied by using numerical models RMA2. This module is one of the open channel flow modeling module contained in software Surfacewater Modeling System8.1. Performed numerical models in SMS8.1, the bathymetry of the river and bay as the input geometry, the average discharge as upstream inputs and yearly tidal average as well as simulating the input down stream flow with variation value of n. Based on the simulation results of SMS8.1, changes in water level gradually decrease from the basin to the estuary and ocean regions. Variation of the value of n to the water level did not change significantly due to any increase in the value of n 0.0050.00002 to 0.00006 m water level in the estuary. Flow velocity in the river is relatively large and gradually tapers to the estuaries and the sea. Variation of the value of n tends to flow velocity did not change significantly due to any increase inflow velocity of 0.005 n value changed from 0.0002 to 0.0008m /s at the estuary.